The availability of management accounting information and its usefulness to managers in the manufacturing sector / Noraizah Abu Bakar - Abu Bakar, Noraizah (2001)
This study reports on the usefulness of MAIS and the availability of information to the operation managers in the manufacturing sectors. The study will categorize the information into four dimensions that are scope, timeliness, aggregation and integration. It is adopted from an earlier research carried out by Chenhall and Morris. Survey for the study has been conducted in the state of Johore involving three regions namely Segamat, Tangkak and Muar. The relationship between the availability of information to managers and how they make use of such information is very important for decision-making process especially for those in managerial and financial levels. The results for the study indicate that managers perceived all four dimensions information to be useful to them. On the contrary, the study indicates that the availability of information is not considered as an important factor in helping them to make better decisions. The finding further indicates that there is no significant relationship between the availability of information and how managers make use of them.